2013
DOI: 10.1063/1.4826882
|View full text |Cite
|
Sign up to set email alerts
|

A coupled hydro-structural design optimization for hydrokinetic turbines

Abstract: An optimization methodology for a stall regulated, fixed pitch, horizontal axis hydrokinetic turbine is presented using a combination of a coupled hydro-structural analysis and Genetic Algorithm (GA) based optimization method. Design and analysis is presented for two different designs: a constant chord, zero twist blade, and a variable chord, twisted blade. A hybrid approach is presented combining Blade Element Momentum (BEM), GA, Computational Fluid Dynamics (CFD), and Finite Element Analysis (FEA) techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The mesh used for our current study is shown in Figure 2. Our previous CFD simulations [26,29] on the same model turbine demonstrated Reynolds number (based on turbine diameter) converges 2.04×10 5 ; a uniform inlet flow speed of 0.73 m/s was thus chosen for analysis and cross-comparison with previous work [26]. The channel outlet was specified as an outlet boundary condition with the average relative pressure of zero.…”
Section: A Domain and Turbine Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesh used for our current study is shown in Figure 2. Our previous CFD simulations [26,29] on the same model turbine demonstrated Reynolds number (based on turbine diameter) converges 2.04×10 5 ; a uniform inlet flow speed of 0.73 m/s was thus chosen for analysis and cross-comparison with previous work [26]. The channel outlet was specified as an outlet boundary condition with the average relative pressure of zero.…”
Section: A Domain and Turbine Model Descriptionmentioning
confidence: 99%
“…Reynolds-averaged Navier-stokes equations with κ-ω SST turbulence model with curvature correction (CC) was solved [30,31]. A multiple reference frame technique is adopted similar to our previous studies [26,29]; a rotation frame (in our case, the inner fluid domain) takes into account the effect of turbine rotation by transforming an unsteady flow in inertial frame (stationary) to a steady flow in non-inertial frame (rotating). The mass and momentum conservation equations can be written as…”
Section: B Governing Equations and Non-dimensional Parametersmentioning
confidence: 99%
“…A moving reference frame was, therefore, incorporated to take the blade rotation into account and transform the unsteady flow in an inertial (stationary) frame to a steady flow in the non-inertial (moving) frame. When a moving reference frame is activated, the equations of motions are modified to incorporate the additional acceleration terms which occur due to the transformation from the stationary to the moving reference frame [23][24][25]. Solving these equations in a steady state manner, the flow around the moving parts can be modeled.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The molecular viscosity (µ ef f ) is the sum of the dynamic viscosity (µ) and turbulent viscosity (µ t ); being calculated from a representative turbulence model. Among different turbulence models existing in the literature, the k − ω shear stress transport (SST) model was chosen for the analysis due to its capability of providing accurate flow-field predictions under adverse pressure gradient and separated flow conditions, both, conditions considered as prevalent in hydrokinetic turbine performance [23,[26][27][28][29].…”
Section: Governing Equationsmentioning
confidence: 99%
“…The benefits of multiblades rotors (more than three blades) relative to axial flows is that they have self‐starting capabilities , and offers a better power‐dimensions ratio. These benefits, combined with the profile S1223 hydrofoil, have allowed us to conduct an investigation of various rotors with different numbers of blades.…”
Section: Hydrofoil and Rotormentioning
confidence: 99%